Literature Review; The Importance of Family Center Care to Increase Child Resilience During Covid 19 Pandemic - Ika Rizki Anggraini; Lia Novitasari (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2021)
Introduction: The condition of covid infects all walks of life, not worrying for children. The role of the family is needed to maintain the resilience of children in preventing the transmission of covid 19 Objectives: This research aims to review the importance of Family Center Care to Increase child resilience during the covid 19 pandemic. Methods: This research applied a literature study. Literature was searched from 4 databases, namely Google Scholar, PubMed (NCBI). Results: Family Center Care is an approach applied for children during the COVID-19 pandemic condition. Its implementation requires parents to do their roles to provide various matters to improve the knowledge, skills, capabilities, health, understanding, and prevention of COVID-19. On the other hand, it has a procedural challenge that could be solved by parents by applying an excellent coping strategy. Conclusions: Family Center Care is an excellent approach for children in this COVID-19 pandemic. The research focus was to observe the parents that were the closest people to children. Their existences could facilitate the psychological needs for security and quality of health. The family center cares actively involve parents and identifies or facilitates the most appropriate need for children in minimizing the children's anxiety.